The “Fight for 15”: Can the Organizing Model that Helped Pass Seattle’s $15 Minimum Wage Legislation Fill the Gap Left by the Decline in Unions? - Mary Hannah (Washington University Journal of Law & Policy, 2016)
This Note examines whether the organizational methods successfully employed by the “Fight for 15” fast-food worker movement in Seattle is the answer to protecting these workers generally. Hannah addresses the historic inability for fast-food franchisees to unionize under the NLRA and advocates for new organizational methods and advocacy. Hannah argues that low-income workers need to expand the use of worker centers and workers’ councils in order to effectively protect the rights of fast-food workers.
Keywords: Fight for 15; NLRA; minimum wage; fast-food worker; unions; low- income workers; National Labor Relations Act; National Labor Relations Board; NLRB; poverty